2020
DOI: 10.1097/pts.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for an Influenza Pandemic: Hospital Acceptance Study of Filtering Facepiece Respirator Decontamination Using Ultraviolet Germicidal Irradiation

Abstract: Objectives: Predictions estimate supplies of filtering facepiece respirators (FFRs) would be limited in the event of a severe influenza pandemic. Ultraviolet decontamination and reuse (UVDR) is a potential approach to mitigate an FFR shortage. A field study sought to understand healthcare workers' perspectives and potential logistics issues related to implementation of UVDR methods for FFRs in hospitals. Methods: Data were collected at three hospitals using a structured guide to conduct 19 individual interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Two studies analysed the determinants related to provider uptake of decontamination. 61 62 Nemeth et al 61 evaluated user acceptance of FFR decontamination, noting that perceived safety of UV decontamination was higher in comparison to wearing an FFR for an extended period of time without decontamination. 61 Viscusi et al 62 reported that decontamination with UV, moist heat or microwave steam did not significantly change the user experience.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies analysed the determinants related to provider uptake of decontamination. 61 62 Nemeth et al 61 evaluated user acceptance of FFR decontamination, noting that perceived safety of UV decontamination was higher in comparison to wearing an FFR for an extended period of time without decontamination. 61 Viscusi et al 62 reported that decontamination with UV, moist heat or microwave steam did not significantly change the user experience.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were ranked as medium to high risk for bias. Fisher et al, 47 Fisher and Shaffer, 109 Heimbuch et al, 52 Lin et al, 54 Mills et al, 48 Nemeth et al, 61 Bergman et al, 56 Lin et al, 53 Lindsley et al, 60 Lore et al, 50 Richter et al, 51 Salter et al, 55 Viscusi et al, 55 Viscusi et al, 57 Viscusi et al, 62 Vo et al, 111 Woo et al, 110 Heimbuch et al 49 (2) Reuse of disposable masks 63-65 70-72 Reuse of disposable masks without decontamination or disinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…decontamination must account for actual clinical practice, regulations, and financial considerations. so that UVGI may mitigate potential FFR shortages in a pandemic[ 26 ]…”
Section: Methodsmentioning
confidence: 99%
“…Kirubarajan et al [ 20 ] revealed numerous strategies that had been evaluated for overcoming a limited supply of personal protective equipment during pandemics or epidemics. They grouped the strategies into six main categories: (1) decontamination of disposable masks [ 21 , 22 , 23 ], (2) reuse and/or extended wear of disposable masks [ 24 , 25 , 26 , 27 ], (3) layering of masks [ 28 , 29 ], (4) introduction of reusable respirators [ 29 , 30 ], (5) use of non-traditional replacements or modifications to masks [ 31 , 32 ], and (6) use of stockpiled or expired masks [ 33 , 34 , 35 ]. However, none of the above-mentioned studies discussed the mechanism of allocating masks.…”
Section: Literature Reviewmentioning
confidence: 99%